Microwave vacuum drying of low-moisture part-skim mozzarella: Process parameters and sample geometry affect product characteristics - B. Gong; J. Dumpler; C.I. Moraru (Journal of Dairy Science)
ABSTRACT: Microwave vacuum drying (MVD) is a promising technology that can be used for creating cheese puffs. In this study, the effects of vacuum level (2–14 kPa), specific microwave power input (1–3 W⋅g−1), and sample geometry on the drying and expansion behavior of low-moisture, part-skim mozzarella cheese during MVD were investigated. The created MVD cheese puffs' moisture content, water activity, area ratio, texture, and color were determined. Vacuum level had the greatest influence on expansion (1.74–3.59 area ratio) but minimal effect on drying, with an optimum puffing range between 6 and 10 kPa. Microwave power input and sample geometry had the greatest effect on drying (6–12% wet basis final moisture was achieved), but minimal effect on expansion. The cheese puffs' texture was largely determined by their moisture content and internal structure and degree of expansion. Limited browning occurred during the MVD process, especially for the smallest sized samples. Overall, this study shows how MVD processing conditions can be optimized for the drying and puffing of cheese, which can help dairy processors use this technology to manufacture dried cheese snacks to meet consumer preferences.